1993
DOI: 10.1172/jci116290
|View full text |Cite
|
Sign up to set email alerts
|

Transinhibition of C1 inhibitor synthesis in type I hereditary angioneurotic edema.

Abstract: To ascertain the mechanism for decreased synthesis ofC1 inhibitor (Cl INH) Clin. Invest. 1993.91:1258-1262

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 16 publications
2
32
0
1
Order By: Relevance
“…Patients with HAE catabolize C1-INH faster than normal subjects, 16 but concomitant downregulation of the normal allele may also occur, at least with some mutations. [17][18][19] Most mutations that cause HAE are point mutations resulting in single amino acid substitutions. 10 Independent families rarely possess identical mutations.…”
Section: The Genetics Of Hereditary Angioedemamentioning
confidence: 99%
“…Patients with HAE catabolize C1-INH faster than normal subjects, 16 but concomitant downregulation of the normal allele may also occur, at least with some mutations. [17][18][19] Most mutations that cause HAE are point mutations resulting in single amino acid substitutions. 10 Independent families rarely possess identical mutations.…”
Section: The Genetics Of Hereditary Angioedemamentioning
confidence: 99%
“…It was first thought that catabolism of the normal protein causes this reduction in activity (40). However, it has also been suggested that the mutant C1INH may transinhibit the normal gene (41) or there may be decreased secretion of C1INH (33,42). Type II HAE is evident in 15% of HAE patients and is characterized by normal or raised antigenic levels of C1INH that have diminished function (43).…”
Section: Introductionmentioning
confidence: 99%
“…The structural abnormalities of C1INH gene in patients with HAE type I are very heterogeneous, including point mutations, deletions and insertions that lead to an unstable and easily degraded mRNA, and an apparent failure to synthesise or secrete the C1INH protein (8)(9)(10). However, mutations abolishing the physiological stop codon are rare, and such mutations have not been reported as a cause of C1INH deficiency.…”
Section: Resultsmentioning
confidence: 99%